Застосування методу детального картування при дослідженні структури популяцій рідкісних видів рослин-геофітів - Gaponenko, M.B.; Gnatiuk, A.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
We propose a method for detailed mapping, which is a diagrammatic representation of individuals in the population with the designation of their ontogenetic and age features, as well as changes in the spatial distribution of plants and can be used at the study of populations of rare species geophytes.